MELATIH KEMANDIRIAN ANAK USIA DINI MELALUI PEMBERIAN PUJIAN PADA ANAK KELOMPOK A1 DI TK PERTIWI GANJAR AGUNGTAHUN PELAJARAN 2014/2015 - Feri Sulistyowati (Lembaga Penelitian UM Metro, 2016)
Self- autonomy needs to be developed in the children’s early ages. The main conditions in facilitating the early children to be aotonomous are self confidence on their own abilities and strength. Giving complement can be one of the other gaod ways to train the children’n self-autonomy from their early ages. Complement is a form of showing love and care. The children’s early ages are the best moment to develop their self-autonomy as they are still in their sensitive psychological growth and their basic life skill development. Training the early children on self-autonomy by giving complement can triger them to do positive things and optimally develop all the potentials with their own awareness